Analisis Pengawasan Serta Pengaruh Kawasan Berikat Terhadap Arus Kas, Beban Pajak Dan Aktivitas Ekspor Pt.Xyz - Deby Valentina (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Free Trade Area ( FTA ) is a part of globalization. In order to support the economy, Indonesian government provides many facilities in taxation. One of them is through the bonded zone facility. Bonded zone is given to company which using export as their main activities. In this research, the authors want to analyze the supervision of this facility and the influence of the bonded zone toward cash flow, tax expenses and export activity of PT. XYZ. This study used descriptive qualitative method, where the author observed directly in the field through interviews. Primary data used are interview and literatures, documents of PT. XYZ and regulation used as secondary data. This study limits the period of PT. XYZ before accepting the bonded zone facility and afterhand, ie 2016-2017. The results of this research found that there is still a weakneeses in terms of supervision but the savings in terms of taxation need to be considered. Therefore, the authors analized that this bonded area facility is worth maintaining.